Quality by Design-Guided Development of Ketoprofen-Cationic Aspasomes Unlocks the Antifungal Potential of Repurposed Ketoprofen for Topical Therapy - Moaz A Eltabeeb; Rofida Albash; Mariam Hassan; Sadek Ahmed; Ahmed M. Agiba; Azza A. K. El-Sheikh; Diana E. Aziz (Pharmaceuticals, 2026)
Background/Objectives: Cutaneous fungal infections remain a major therapeutic challenge due to poor skin penetration and emerging antifungal resistance of current treatments. Drug repurposing offers a promising strategy to expand antifungal therapy, with ketoprofen (KPN) recently demonstrating antifungal activity. Methods: In this study, KPN-cationic aspasomes (Ca-ASPMs) were developed using a Quality by Design (QbD) approach to enhance topical delivery and maximize the therapeutic potential of repurposed KPN. A D-optimal experimental design was implemented to investigate the influence of ascorbyl palmitate amount (X1), ethanol concentration (X2), and cationic SAA type (X3) on the critical quality attributes of KPN-Ca-ASPMs, namely entrapment efficiency, particle size, and zeta potential. Results: Numerical optimization identified an optimum formulation comprising 10 mg ascorbyl palmitate, 5% ethanol, and didodecyldimethylammonium bromide (DDAB) as cationic SAA, with an overall desirability of 0.815. The optimal KPN-Ca-ASPM (F9) exhibited nanosized vesicles (213.24 ± 2.20 nm) and 91.30 ± 10.01% entrapment efficiency. TEM confirmed the spherical morphology of the vesicles, while DSC demonstrated successful incorporation of KPN within the aspasomal matrix. F9 exhibited enhanced in vitro drug release (68% after 6 h) and excellent storage stability. Confocal laser scanning microscopy demonstrated enhanced skin penetration of F9. In a murine cutaneous candidiasis model, F9 significantly enhanced the antifungal efficacy of KPN, producing a 2.989-log reduction in fungal burden compared with the untreated group and significantly outperforming the free drug (p = 0.0005). Histopathological examination confirmed restoration of normal skin architecture. Conclusions: Collectively, the QbD-guided development of KPN-Ca-ASPM provided a reproducible nanocarrier that significantly enhanced the topical antifungal efficacy of repurposed KPN, highlighting its potential for the treatment of cutaneous candidiasis.